Peran Green Accounting dalam Mendukung Keberlanjutan Lingkungan: Studi Kasus PT Darma Satya Nusantara Tbk (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to evaluate the role of green accounting in supporting environmental sustainability at PT Dharma Satya Nusantara Tbk (DSNG). Using a qualitative case study approach, the research analyzes the company's sustainability reports. The results indicate that DSNG systematically records environmental costs and investments, including the conservation of 8,733 hectares of forest, the use of renewable energy, and the implementation of the NDPE (No Deforestation, No Peat, No Exploitation) policy. DSNG also engages local communities through training and sustainable forestry programs. The implementation of green accounting enhances the company’s transparency, accountability, and reputation, while also contributing to the achievement of the Sustainable Development Goals (SDGs). Green accounting has proven to be a strategic tool for promoting comprehensive and long-term sustainable performance in the agribusiness sector.